Konstruksi media “CNN Indonesia” dan “Republika” perspektif Murray Jacob Edelman: Studi komparatif framing - Hasna, Nida Asyfiatul (Maliki Interdisciplinary Journal, 2024)
Mass media presents reality framed in a structure. Behind media construction there is the role of the editor who creates the framing of the news according to his point of view. This research aims to determine the news framing model constructed by the editor of each news story based on Murray Jacob Edelman's perspective which consists of categorization, ideology, rubrication and classification. This research is a type of qualitative research. The research results found that the editors of each news story had different perspectives in framing the same news.